1996
DOI: 10.1159/000292043
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Adenocarcinoma in Early Pregnancy

Abstract: Adenocarcinoma of the endometrium with intrauterine pregnancy is extremely rare. We report the case of a 35-year-old woman with endometrial cancer discovered in the 7th gestational week. A therapeutic abortion was performed and because of bleeding and spotting dilatation and curettage was done 10 days later. Histology revealed adenocarcinoma in addition to products of conception. Hysterectomy and bilateral salpingo-oophorectomy was performed 3 weeks after intracavitary radiotherapy. Because of superficial myom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…A total of 18 studies with 25 cases of EC associated with pregnancy (including our case) have been reported [3, 520]; 9 cases were identified postpartum up to the 14-month; 16 cases were diagnosed at the time of D&C for first-trimester spontaneous or elective abortion. These results suggest that clinicians should consider EC after pregnancy even though abnormal bleeding is often observed after pregnancy, and EC associated with pregnancy is rare.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 18 studies with 25 cases of EC associated with pregnancy (including our case) have been reported [3, 520]; 9 cases were identified postpartum up to the 14-month; 16 cases were diagnosed at the time of D&C for first-trimester spontaneous or elective abortion. These results suggest that clinicians should consider EC after pregnancy even though abnormal bleeding is often observed after pregnancy, and EC associated with pregnancy is rare.…”
Section: Discussionmentioning
confidence: 99%